A Functional Platform for the Detection of JWH‐073 as a Model for Synthetic Cannabinoids. Issue 9 (13th March 2018) - Sengel, Tulay Yilmaz; Celik, Emine Guler; Aydogan, Cansu; Gumus, Zinar Pinar; Ilktac, Raif; Aydindogan, Eda; Ciftci, Mustafa; Aldemir, Ebru; Coskunol, Hakan; Timur, Suna; Yagci, Yusuf
Abstract: During the last decade, progress has been made in the on‐site detection of abused drug use. Herein, we present an electrochemical biosensor for the detection of one of the synthetic cannabinoids (SCs), JWH‐073, using poly (methyl methacrylate) (PMMA) hyperbranched copolymer (HBC) as a base coating and antibody molecules to bind the JWH‐073 to the surface. Modification of the surface is proved with various techniques such as differential pulse voltammetry, cyclic voltammetry, and electrochemical impedance spectrometry. The limit of detection and linearity (in logarithmic scale) for JWH‐073 were found to be 31.87 ng/mL and 25–500 ng/mL, respectively. The selectivity of the proposed biosensor was also tested in the presence of interfering molecules and the response was much higher for JWH‐073 in all measurements. In the final part of the study, synthetic urine was tested with the device and the relative standard deviation value was calculated to be less than 5.0 %. The confirmation of data from the resulting bio‐platform was performed via LC‐QTOF/MS. This work is the first of its kind, a novel, rapid, cost‐effective sensing platform for the detection of the SC. Abstract : Drug watch : A functional surface is designed for the practical detection of a synthetic cannabinoid model. The sensor can easily be miniaturized and adapted to analyze various illicit drugs.